2015
DOI: 10.1099/vir.0.000117
|View full text |Cite
|
Sign up to set email alerts
|

Detection of exosomal prions in blood by immunochemistry techniques

Abstract: In most forms of prion diseases, blood is infectious, but detection by immunochemistry techniques of the only available marker of infection (the misfolded prion protein, PrP TSE ) in blood remains elusive. We developed a novel method for the detection of PrP TSE in blood of prion-infected rodents based on the finding that PrP TSE is associated with plasma exosomes.However, further purification of the exosomes on a sucrose gradient was necessary to remove plasma immunoglobulins, which interfere with PrP TSE , m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…In addition, there is evidence that macrophages can phagocytose and translocate Aβ seeds (Eisele et al, 2014; Cintron et al, 2015). Small, cell-derived extracellular vesicles such as exosomes have been linked to the transmissibility of PrP-prions (Fevrier et al, 2004; Properzi et al, 2015; Guo et al, 2016a). Extracellular vesicles also have been suggested to ferry Aβ between cells (Rajendran et al, 2006), although their influence on the pathogenesis of AD – positive or negative - remains uncertain (Joshi et al, 2015).…”
Section: The Prion-like Properties Of Aggregated Aβmentioning
confidence: 99%
“…In addition, there is evidence that macrophages can phagocytose and translocate Aβ seeds (Eisele et al, 2014; Cintron et al, 2015). Small, cell-derived extracellular vesicles such as exosomes have been linked to the transmissibility of PrP-prions (Fevrier et al, 2004; Properzi et al, 2015; Guo et al, 2016a). Extracellular vesicles also have been suggested to ferry Aβ between cells (Rajendran et al, 2006), although their influence on the pathogenesis of AD – positive or negative - remains uncertain (Joshi et al, 2015).…”
Section: The Prion-like Properties Of Aggregated Aβmentioning
confidence: 99%
“…Both normal (PrP c ) and pathological (PrP sc ) prion proteins are incorporated into EVs by normal and prion-infected cells (51,52). PrP sc -carrying EVs are present in biological fluids (i.e., blood) of infected animals (53,54), and these PrP sc -carrying EVs can spread prion infection to normal recipient cells (55). These findings have opened up new and important insights into the complicated mechanisms of transmission and propagation of prion diseases.…”
Section: Evs In Physiology and Pathology Of The Nervous Systemmentioning
confidence: 99%
“…We and others showed that prion-infected cultured cells actively secrete exosomes bearing misfolded PrP protein and prion infectivity [25][26][27][28][29][30][31]. Similarly, several pathological misfolded proteins like Tau, a-synuclein, SOD1, TDP-43 or the Ab peptide involved in the neurodegenerative diseases cited above were found to be released in association with exosomes, thus highlighting that a range of prion-like proteins with seeding activity may gain access to the extracellular space through their association with exosomes that can participate to their spreading [9,24,[32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%